2019
DOI: 10.3390/f10050390
|View full text |Cite
|
Sign up to set email alerts
|

Overhead Protection Increases Fuel Quality and Natural Drying of Leaf-On Woody Biomass Storage Piles

Abstract: Short-rotation woody crops (SRWC) have the potential to make substantial contributions to the supply of biomass feedstock for the production of biofuels and bioproducts. This study evaluated changes in the fuel quality (moisture, ash, and heating value) of stored spring harvested shrub willow (Salix spp.) and hybrid poplar (Populus spp.) chips with respect to pile protection treatments, location within the storage piles, and length of storage. Leaf-on willow and poplar were harvested in the spring, and wood ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…This is especially true when willow occupies lower quality land with somewhat poorly to very poorly drained soil. In addition, difficulties securing and mobilizing equipment on short notice have caused some commercial growers to start harvesting in the late summer or early fall (Eisenbies, Volk, Therasme, & Hallen, 2019; Therasme, Eisenbies, & Volk, 2019). In other words, they are placing more importance on ground conditions and being able to complete harvests than on concerns about potential impacts of harvesting during the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true when willow occupies lower quality land with somewhat poorly to very poorly drained soil. In addition, difficulties securing and mobilizing equipment on short notice have caused some commercial growers to start harvesting in the late summer or early fall (Eisenbies, Volk, Therasme, & Hallen, 2019; Therasme, Eisenbies, & Volk, 2019). In other words, they are placing more importance on ground conditions and being able to complete harvests than on concerns about potential impacts of harvesting during the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…The sampling points were placed at 1.5-2.5 m apart of each other along the length of the pile. A total of eight temperatures probes connected to two data loggers (HOBO U12-008) were inserted in the shell and core of the piles following the description provided by Eisenbies et al (2016) and Therasme et al (2019). Data loggers inserted in this storage pile automatically recorded the pile temperature every 30 min.…”
Section: Winter Storage Pilementioning
confidence: 99%
“…But, moisture content increases during autumn and winter storage (Filbakk et al, 2011). The moisture content of uncovered willow chip storage piles harvested in late spring with a moisture content of 46% decreased to 37-26% after 60 days of storage and increased thereafter until the end of the storage trial in mid-autumn (Therasme et al, 2019). However, Eisenbies et al (2016) reported an increase of moisture from 42% at harvest in February to 49% in May and 44% in July.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations